Pengaruh Urgensi dan Kenyamanan Belanja Online Menjelang Lebaran Terhadap Keputusan Pembelian Produk Fashion pada Konsumen Tiktok Shop - Permata Sari, Linda; Suharini (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
Eid al-Fitr is increasingly experiencing a shift in meaning, transitioning from a purely religious celebration to one marked by heightened commercialization, especially in the fashion sector. As the holiday Eid approaches, consumers demonstrate a growing urgency to purchase fashion products reflects consumers' urgency to fulfill their appearance needs. This study aims to examine the influence of urgency and online shopping convenience on fashion product purchasing decisions among TikTok Shop consumers. A quantitative descriptive method was used with a total of 122 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using SPSS version 26. The results indicate that urgency has a positive and significant effect on purchasing decisions with a t-value of 5.260 > t-table 1.980, and online shopping convenience also has a significant effect with a t-value of 5.062 > t-table 1.980. Simultaneously, the F-value obtained was 39.813 > F-table 3.07, with a coefficient of determination (R²) of 0.401, indicating that both variables influence purchasing decisions by 40.1%. This study suggests that TikTok Shop needs to improve services such as the checkout process, transaction security, and user interface convenience. Furthermore, sellers are encouraged to apply urgency-based strategies, such as limited-time offers, to increase consumer purchase intention.